Las estrategias LÚDICAS en el área Lógico Matemático para el desarrollo del pensamiento nocional de niños de 04 años - Díaz Grández, Gésigry (2006)
Human thought represents missing facts and events of the current situation, while designing the future; ie, representations and projections depend on thought. This thought is built up gradually and the onset is the notional thought; then conceptual thinking; then the categorial thought. According to several scholars, they show that notions are essential tools for the general knowledge of things or objects that possess the properties defined for each image. In that sense, the notional thought allows children to think with propositions, for it is taken into consideration in concretions thinking abilities or intellectual capacities notional amounts. Children are incapable of thinking in abstractions. This is an intellectual restriction for children. The notions that children should develop during their education are: The notion of color that facilitates relatively complete and authentic objects of perception. This notion is through the handling things, elements, work tools, etc .; the notion of form perceives the shape of objects and develops visual explorations; the notion of size and weight sets differences, similarities and perceptual and conceptual promote development; the notion of magnitude is the raw material that should be used to guide the child in the progressive acquisition of the notions of length, area, weight, time; the notion of space structure linked to child space knowledge, it allows the child to know the world around him; the notion of serialization order elements according to a given dimension by establishing relationships between them. This capability is also needed in the construction of the concept of number; the notion of classification can sort your world and your thinking illogically, that respond to different criteria; the notion of correspondence establishes comparisons between two sets and related items; the notion of .entidades and / or lot number used quantifiers little more, etc. account, sets, groups, recognizes and numbers. Situations where they make physical and logical concepts, based on their own interests, also do not consider that the construction of its concepts do not perform alone, but in relation to the world around them. For this reason, we are motivated to make this monograph and which would be a suitable alternative in using recreational strategies because the game becomes the most natural child's learning way through them learn to grasp among others things mathematical ideas and develop their notional thought relevant and effective. If educational institutions develop the notional thinking, then we will be promoting children with comprehensive development in their capacities as the notional thought is the point where the child or the child part, are particular things and events that are constructed between two seven years old, is characterized by the symbolic activity as given in their games and attempts to use the reasoning expressed in words. These two aspects of primitive thought will be transformed later in creative imagination and rational thinking respectively. With the support of language, logic is gradually and pre-concepts gain in generality and accuracy through constant both verbal and concrete experiences. At present the learning process based on the new pedagogical approach suggests that the student is builder of his own knowledge and is produced from imbalances and cognitive conflicts that modify the cognitive schemata of knowledge. Therefore, all education must be based on concrete forms, real directly perceived by the senses. The child needs to express something before internalizing a situation and live it, experience feelings, activities that have personal significance, it is essential for the activity to be effective and teaching condition optimal results. The work is structured as follows: Chapter I deals with the notional thought, it is conceptualized and the process and development of this thinking is based